Efficacy and Safety of Endoscopic Third Ventriculostomy in Obstructive Hydrocephalus - Gautam, Sachidanad; Kamble, Sumit (Nepal Journal of Neuroscience, 2017)
Endoscopic third ventriculostomy is the procedure of choice to treat obstructive hydrocephalus now a days. Published case series of endoscopic third ventriculostomy (ETV) for childhood hydrocephalus have reported widely varying success rates. The purpose of this study is to determine the success rate and complications of ETV for treating obstructive hydrocephalus.Patients with obstructive hydrocephalus and already shunted patients for obstructive hydrocephalus presented with blocked shunt were included in the study. The exclusion criteria consisted ofrecurrent tumor or intra ventricular hemorrhage. Endoscopic third ventriculostomy was performed. Patients were followed up for one year and Clinical and Radiological improvement, complications and mortality was noted. This study was conducted in Neurosurgery Department, Govt. Medical College, Kota between 2015-2016.There were 56 patients including 36 males and 20females. Success rate in the form of clinical and/ or radiological improvement was seen in 88.8% 0f patients. Complications were seen in 6 patients including ETV failure and ventricular hemorrhage. There was no mortality during follow up period of 1 year.ETV is cost effective and safe procedure in patients with obstructive hydrocephalus with good outcome. It may be used as replacement procedure of ventriculo-peritoneal shunt as initial line of management in selected patients based on ETV score. Nepal Journal of Neuroscience, Vol. 14, No. 2,  2017 Page: 21-24